Manufacturing method of microcrystalline glass product
Through mask exposure and crystallization heat treatment, microcrystalline glass is formed and chemical strengthening process is carried out, which solves the problems of reduced strength, difficulty in processing and high cost of microcrystalline glass products in the prior art, and realizes efficient manufacturing of microcrystalline glass products with blackened parts and transparent parts.
Patent Information
- Application Number
- CN202411924764.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-22
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively manufacture microcrystalline glass products with blackened parts and transparent parts, and there are problems of reduced strength, difficult processing and high cost.
The manufacturing method of microcrystalline glass products is adopted, including forming matrix glass, forming microcrystalline glass by mask exposure and crystallization heat treatment, and then undergoing chemical reinforcement process processing to prepare a microcrystalline glass product with a blackened part and a transparent part.
The excellent mechanical properties of microcrystalline glass products are achieved. The transparent part has a high transmittance in the visible light band, and the blackened part has a low transmittance in the visible light band, which reduces production costs and improves the feasibility of processing.
Smart Images

Figure BDA0005208970980000151 
Figure BDA0005208970980000201 
Figure BDA0005208970980000211
Abstract
Description
[0001] This application is a divisional application for the invention patent application with application number 202410483551.1, application date April 22, 2024, and name “Microcrystalline glass, microcrystalline glass products and manufacturing methods thereof”. Technical Field
[0002] The invention relates to a method for manufacturing a microcrystalline glass product, in particular to a method for manufacturing a microcrystalline glass product having a blackened part and a transparent part. Background Art
[0003] In recent years, with the continuous rise and development of consumer electronic products, glass, as a transparent and high-performance material, has been widely used in electronic devices. Since electronic devices have many sophisticated electronic components inside, they need to be provided with a cover or a shell to protect the internal electronic components. With the diversification of market demand, the use scenarios of protective cover glass are becoming more and more complex, and its role is no longer just to protect the internal electronic components, but sometimes it also needs to have other functions. For example, in the vital signs monitoring of smart watches, the glass material needs to be partially transparent, but it needs to be shielded in other places to avoid the interference of stray light. Therefore, the glass material needs to have both black and transparent parts, which poses new challenges to the glass manufacturing process technology. In the prior art, the above-mentioned cover material can be manufactured by embedded design using two different materials, transparent and black, but due to the different strengths of the two materials, the large difference in expansion coefficients, and the need to process through holes, there are microcracks on the inner wall of the glass, which reduces the strength of the cover material, and it is difficult to process smaller holes or special-shaped graphics, and the production cost is high. Summary of the invention
[0004] Based on the above reasons, the technical problem to be solved by the present invention is to provide a method for manufacturing a microcrystalline glass product, wherein the method can be used to manufacture a microcrystalline glass product having a blackened portion and a transparent portion.
[0005] The solution adopted by the present invention to solve the technical problem is:
[0006] (1) A method for manufacturing a microcrystalline glass product, the method comprising the following steps: forming a matrix glass, subjecting the matrix glass to a crystallization process to form a microcrystalline glass, and then subjecting the microcrystalline glass to a chemical strengthening process to form a microcrystalline glass product, wherein the crystallization process comprises subjecting the matrix glass to a mask exposure process and then to a crystallization heat treatment.
[0007] (2) The method for manufacturing a microcrystalline glass product according to (1), wherein the microcrystalline glass product comprises one or more blackened parts and one or more transparent parts, and the average transmittance T of the transparent part of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm in the wavelength range of 400 to 800 nm is400-800nm The average transmittance T of the blackened part of the 0.2-1.5 mm thick microcrystalline glass product in the 400-800 nm band is 85.0% or more. 400-800nm It is less than 5.0%.
[0008] (3) According to the method for manufacturing a microcrystalline glass product described in (1) to (2), the mask exposure treatment includes ultraviolet exposure of a specific position or area of the matrix glass, the ultraviolet light wavelength is preferably 313 nm, and the exposure time is preferably 5 to 60 minutes.
[0009] (4) According to the method for manufacturing microcrystalline glass products described in (1) to (3), the crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes a nucleation process at a first temperature and then a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.
[0010] (5) According to the method for manufacturing a microcrystalline glass product according to any one of (1) to (4), the chemical strengthening process includes immersing the microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.
[0011] (6) According to the method for manufacturing a microcrystalline glass product described in any one of (1) to (5), the average transmittance T of the transparent part of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm in the wavelength range of 400 to 800 nm is 400-800nm is 88.0% or more, preferably 90.0% or more, more preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2-1.5 mm in the 400-800 nm wavelength range 400-800nm is 3.0% or less, preferably 1.5% or less, more preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm at 870 nm 870nm is 15.0% or less, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm at 940 nm 940nmIt is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.
[0012] (7) The method for producing a glass-ceramic product according to any one of (1) to (6), wherein the blackened portion of the glass-ceramic product contains a crystalline phase, and the transparent portion of the glass-ceramic product does not contain a crystalline phase.
[0013] (8) According to the method for manufacturing a microcrystalline glass product according to any one of (1) to (7), the blackened portion of the microcrystalline glass product contains a lithium metasilicate crystalline phase. In the blackened portion of the microcrystalline glass product, the weight percentage of the lithium metasilicate crystalline phase is preferably 5 to 50%, more preferably 5 to 40%, and further preferably 10 to 30%.
[0014] (9) The method for manufacturing a glass-ceramic product according to any one of (1) to (8), wherein the components of the glass-ceramic product, expressed in weight percentage, include: SiO2: 65-78%, preferably SiO2: 68-77%, more preferably SiO2: 69.5-75.5%; R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-15%. 12%; Al2O3: 3-12%, preferably Al2O3: 4-10%, more preferably Al2O3: 5-9%; ZrO2: 1.5-10%, preferably ZrO2: 2-8%, more preferably ZrO2: 3-6.5%; CeO2: 0.01-0.6%, preferably CeO2: 0.07-0.4%, more preferably CeO2: 0.08-0.3%; Ag2O: 0.01-0.8%, preferably Ag2O: 0.1-0.6%, more preferably Select Ag2O: 0.2-0.5%; Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%; MO: 0-5%, preferably MO: 0-3%, more preferably MO: 0-1%, more preferably no MO; Ln2O3: 0-5%, preferably Ln2O3: 0-3% , more preferably Ln2O3: 0-1%, further preferably no Ln2O3; Fe2O3: 0-1%, preferably Fe2O3: 0-0.5%, more preferably Fe2O3: 0-0.2%, further preferably no Fe2O3, the R2O is one or two of Na2O, K2O, MO is one or more of MgO, CaO, SrO, BaO, ZnO, Ln2O3 is one or more of La2O3, Gd2O3, Y2O3.
[0015] (10) According to the method for manufacturing a glass-ceramic product according to any one of (1) to (9), the components of the glass-ceramic product, expressed in weight percentage, meet one or more of the following 14 conditions:
[0016] 1) SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, and more preferably SiO2 / Li2O is 7.0 to 8.5;
[0017] 2) (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6;
[0018] 3) (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5;
[0019] 4) Ag2O / CeO2 is 1.0 to 10.0, preferably Ag2O / CeO2 is 1.5 to 6.5, and more preferably Ag2O / CeO2 is 2.0 to 4.5;
[0020] 5) Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0;
[0021] 6) (SiO2 + Li2O) / ZrO2 is 8.0 to 55.0, preferably (SiO2 + Li2O) / ZrO2 is 10.0 to 37.0, more preferably (SiO2 + Li2O) / ZrO2 is 12.0 to 25.0, and further preferably (SiO2 + Li2O) / ZrO2 is 13.0 to 20.0;
[0022] 7) ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0;
[0023] 8) (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 20.0, more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0 to 12.5, and further preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0;
[0024] 9) (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2;
[0025] 10) SnO2 / (CeO2+SnO2) is 0 to 0.9, preferably SnO2 / (CeO2+SnO2) is 0 to 0.6, and more preferably SnO2 / (CeO2+SnO2) is 0 to 0.5;
[0026] 11) R2O+Li2O+Al2O3 is 15-30%, preferably R2O+Li2O+Al2O3 is 17.5-29.5%, more preferably R2O+Li2O+Al2O3 is 18.5-26%, and further preferably R2O+Li2O+Al2O3 is 20-25%;
[0027] 12) (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and further preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8;
[0028] 13) MO / ZrO2 is 2.5 or less, preferably MO / ZrO2 is 1.5 or less, and more preferably MO / ZrO2 is 0.5 or less;
[0029] 14) Sb2O3+SnO2: 0.05-1.2%, preferably Sb2O3+SnO2: 0.1-1%, more preferably Sb2O3+SnO2: 0.2-0.7%, wherein R2O is one or two of Na2O and K2O, and MO is one or more of MgO, CaO, SrO, BaO and ZnO.
[0030] (11) According to the method for manufacturing a microcrystalline glass product described in any one of (1) to (5), the drop ball test height II of the microcrystalline glass product is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.
[0031] (12) A microcrystalline glass product made by the method for manufacturing microcrystalline glass products described in any one of (1) to (11).
[0032] (13) A glass cover plate comprising the microcrystalline glass product described in (12).
[0033] (14) A device comprising the microcrystalline glass product described in (12) and / or the glass cover plate described in (13).
[0034] The beneficial effect of the present invention is that a microcrystalline glass product having a blackened part and a transparent part can be obtained through the manufacturing method of the microcrystalline glass product of the present invention, and the microcrystalline glass product has excellent mechanical properties, the transparent part has a high transmittance in the visible light band, and the blackened part has a low transmittance in the visible light band. DETAILED DESCRIPTION
[0035] Below, the embodiments of the present invention are described in detail, but the present invention is not limited to the following embodiments, and can be implemented by appropriate changes within the scope of the purpose of the present invention. In addition, about the repeated description part, although there is a situation of appropriate omission of description, the main purpose of the invention will not be limited thereby.
[0036] The glass-ceramics and glass-ceramics products of the present invention are materials having a crystalline phase (sometimes also referred to as crystal) and a glass phase, which are different from amorphous solids. The crystalline phase of the glass-ceramics and glass-ceramics products can be identified by the peak angles appearing in the X-ray diffraction pattern of X-ray diffraction analysis and / or measured by TEMEDX.
[0037] After repeated experiments and studies, the inventors of the present invention obtained the microcrystalline glass or microcrystalline glass products of the present invention by regulating the content and content ratio of specific components constituting microcrystalline glass and microcrystalline glass products to specific values and precipitating specific crystalline phases.
[0038] In some embodiments, the glass-ceramics of the present invention comprises one or more blackened portions and one or more transparent portions, wherein the transparent portions refer to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the microcrystalline glass in the 400-800nm band when the microcrystalline glass is processed into a thickness of 0.2-1.5mm. 400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the microcrystalline glass contains a crystalline phase, and the transparent portion of the microcrystalline glass does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass is uniformly distributed.
[0039] In some embodiments, the glass-ceramic product of the present invention comprises one or more blackened parts and one or more transparent parts, wherein the transparent part refers to the average transmittance (T 400-800nm ) is more than 85.0%, and the blackened part refers to the average transmittance (T) of the microcrystalline glass product in the 400-800nm band when the microcrystalline glass product is processed into a thickness of 0.2-1.5mm. 400-800nm ) is less than 5.0%. In some embodiments, the blackened portion of the microcrystalline glass article contains a crystalline phase, and the transparent portion of the microcrystalline glass article does not contain a crystalline phase. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass article is uniformly distributed.
[0040] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention are entirely blackened, and the blackened portion refers to the average transmittance (T 400-800nm ) is less than 5.0%. In some embodiments, the crystalline phase of the blackened portion of the microcrystalline glass or microcrystalline glass article is uniformly distributed.
[0041] In some embodiments, the glass-ceramics or glass-ceramics products of the present invention are entirely transparent, and the transparent portion refers to the average transmittance (T 400-800nm ) is more than 85.0%.
[0042] In some embodiments, the blackened portion in the glass-ceramics or glass-ceramics products of the present invention may form patterns of any shape and / or size.
[0043] Next, the scope of each component (ingredient) of the matrix glass, microcrystalline glass and microcrystalline glass products of the present invention is described. In this specification, unless otherwise specified, the content of each component is expressed in weight percentage (wt%) relative to the total amount of matrix glass, microcrystalline glass or microcrystalline glass product material converted into oxide composition. Here, the "composition converted into oxide" means that when oxides, composite salts and hydroxides used as raw materials for the matrix glass, microcrystalline glass or microcrystalline glass product components of the present invention decompose and transform into oxides when melted, the total amount of the oxide material is taken as 100%. In addition, in this specification, when it is only referred to as glass, it is the matrix glass before crystallization (i.e., crystallization process treatment), the matrix glass after crystallization (i.e., crystallization process treatment) is called microcrystalline glass, and microcrystalline glass products refer to products obtained after chemical strengthening of microcrystalline glass.
[0044] Unless otherwise indicated in specific cases, the numerical ranges listed herein include upper and lower limits, and "above" and "below" include the endpoints, as well as all integers and fractions within the range, without limitation to the specific values listed when the range is defined. The term "about" as used herein means that the formula, parameters and other quantities and features are not and need not be exact, and may be approximate and / or larger or lower if necessary, reflecting tolerances, conversion factors and measurement errors, etc. "And / or" as used herein is inclusive, for example, "A and / or B" means only A, or only B, or both A and B.
[0045] In some embodiments of the present invention, the crystalline phase (crystal) in the glass-ceramic or glass-ceramic product contains a lithium silicate crystalline phase, preferably a lithium metasilicate crystalline phase (Li2SiO3) crystalline phase. In some embodiments, the lithium metasilicate crystalline phase has a higher weight percentage than other crystalline phases. In some embodiments, the crystalline phase in the glass-ceramic or glass-ceramic product includes only a lithium metasilicate crystalline phase.
[0046] In some embodiments, in the blackened portion of the microcrystalline glass or microcrystalline glass products, the weight percentage of the lithium metasilicate crystalline phase is 5-50%, preferably the weight percentage of the lithium metasilicate crystalline phase is 5-40%, and more preferably the weight percentage of the lithium metasilicate crystalline phase is 10-30%. In some embodiments, in the blackened portion of the microcrystalline glass or microcrystalline glass products, the weight percentage of the lithium metasilicate crystalline phase is 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%.
[0047] SiO2 is a glass-forming oxide and a skeleton that forms glass. It has a low dielectric constant and dielectric loss. SiO2 is a component of lithium metasilicate in microcrystalline glass. When the SiO2 content is less than 65%, the hardness and expansion coefficient of the glass decrease, and the dielectric constant and dielectric loss of the glass increase. When the SiO2 content is higher than 78%, the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products increases. Therefore, the content range of SiO2 is 65-78%, preferably 68-77%, and more preferably 69.5-75.5%. In some embodiments, the SiO2 may include about 65%, 65.5%, 66%, 66.5%, 67%, 67.5%, 68%, 68.5%, 69%, 69.5%, 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, 75.5%, 76%, 76.5%, 77%, 77.5%, 78%.
[0048] Li2O is the main component for forming crystals in the glass-ceramics and glass-ceramics products of the present invention. When the content of Li2O is less than 5%, the crystal content of the glass-ceramics or glass-ceramics products decreases, and the transmittance of the blackened part is higher; when the content of Li2O is greater than 15%, the Young's modulus and the drop ball test height of the glass decrease, and the refractive index and dielectric loss of the glass increase. At the same time, the glass of the part of the matrix glass that is not exposed to ultraviolet light during the crystallization process is easy to crystallize during the heat treatment process, and the transmittance of the transparent part of the glass-ceramics and glass-ceramics products decreases. Therefore, the content of Li2O is limited to 5-15%, preferably 7-13%, and more preferably 8.5-12%. In some embodiments, about 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, 15% Li2O may be included.
[0049] The inventors have found that, in some embodiments, the hardness of the glass and the height of the drop ball test increase with the increase of the SiO2 / Li2O value, and the refractive index decreases with the increase of the SiO2 / Li2O value. At the same time, when SiO2 / Li2O is lower than 5.5, the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products decreases, and the transmittance of the blackened part increases; when SiO2 / Li2O exceeds 10.0, the crystal content of the blackened part of the microcrystalline glass and microcrystalline glass products is low, and the transmittance of the blackened part increases. Therefore, in some embodiments, preferably SiO2 / Li2O is 5.5 to 10.0, more preferably SiO2 / Li2O is 6.0 to 9.0, and further preferably SiO2 / Li2O is 7.0 to 8.5, the transparent part of the microcrystalline glass and microcrystalline glass products has a higher transmittance in the visible light band, and the transmittance of the blackened part is lower, which is particularly suitable for the optical signal channel or light shielding system of electronic products. In some embodiments, the value of SiO2 / Li2O can be 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5, 7.6, 7.7, 7.8, 7.9, 8.0, 8.1, 8.2, 8.3, 8.4, 8.5, 8.6, 8.7, 8.8, 8.9, 9.0, 9.1, 9.2, 9.3, 9.4, 9.5, 9.6, 9.7, 9.8, 9.9, 10.0.
[0050] Alkali metal oxide R2O (R2O is one or both of Na2O and K2O) can promote the precipitation of lithium metasilicate crystals and improve the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products. When the R2O content is less than 2%, the crystal content of microcrystalline glass and microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved; when the R2O content is greater than 12%, the Young's modulus and the drop ball test height of the glass decrease, and the refractive index, dielectric constant and dielectric loss of the glass increase. Therefore, the content of R2O is limited to 2-12%, preferably 3-10%, and more preferably 4-8%. In some embodiments, about 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% R2O may be included.
[0051] Al2O3 can inhibit the decrease in the transmittance of the transparent part of microcrystalline glass and microcrystalline glass products after mask exposure and heat treatment, and improve the strength and hardness of the glass, and enhance the chemical stability of the glass. When the content of Al2O3 is less than 3%, the hardness and Young's modulus of the glass decrease, and the linear expansion coefficient increases; when the content of Al2O3 is higher than 12%, the dielectric constant and dielectric loss of the glass increase, the crystal content of the blackened part of the microcrystalline glass and microcrystalline glass products decreases, and the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. Therefore, the content of Al2O3 is 3-12%, preferably 4-10%, and more preferably 5-9%. In some embodiments, about 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12% of Al2O3 may be included.
[0052] In some embodiments, when the total content of R2O, Li2O and Al2O3 R2O+Li2O+Al2O3 is less than 15%, the refractive index, hardness and Young's modulus of the glass are reduced, and when R2O+Li2O+Al2O3 is greater than 30%, the dielectric constant and dielectric loss of the glass are increased. Therefore, preferably R2O+Li2O+Al2O3 is 15-30%, more preferably R2O+Li2O+Al2O3 is 17.5-29.5%, further preferably R2O+Li2O+Al2O3 is 18.5-26%, and further preferably R2O+Li2O+Al2O3 is 20-25%. In some embodiments, R2O+Li2O+Al2O3 is approximately 15%, 15.5%, 16%, 16.5%, 17%, 17.5%, 18%, 18.5%, 19%, 19.5%, 20%, 20.5%, 21%, 21.5%, 22%, 22.5%, 23%, 23.5%, 24%, 24.5%, 25%, 25.5%, 26%, 26.5%, 27%, 27.5%, 28%, 28.5%, 29%, 29.5%, or 30%.
[0053] The inventors have found through a large number of experimental studies that in some embodiments, by controlling the ratio of the total content of SiO2 and Al2O3 SiO2+Al2O3 to the total content of Li2O, Na2O, and K2O Li2O+Na2O+K2O (SiO2+Al2O3) / (Li2O+Na2O+K2O) in the range of 3.0 to 7.5, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products is lower, and the refractive index of the glass is lower, which can reduce the reflectivity of the light signal on the glass surface and increase the incidence rate of the light signal. Therefore, the preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, the more preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, the further preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and the further preferred ratio of (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8. In some embodiments, the value of (SiO2+Al2O3) / (Li2O+Na2O+KO) may be 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4, 7.5.
[0054] ZrO2 can adjust the accuracy of the black pattern formed by the blackened part of the glass after mask exposure, improve the interface distinction between the exposed part and the unexposed part, and prevent the unexposed part from crystallizing near the interface after heat treatment, so as to maintain the high transmittance of the unexposed part in the visible light band after heat treatment, and ensure that the blackened part has a lower transmittance after heat treatment of the exposed part. When the ZrO2 content is lower than 1.5%, the expansion coefficient of the glass increases, and the unexposed part is easy to crystallize during heat treatment of the glass, resulting in a decrease in the transmittance of the transparent part. When the ZrO2 content is higher than 10%, the crystal content of microcrystalline glass and microcrystalline glass products decreases, the transmittance of the blackened part increases, and even the blackening effect cannot be achieved. Therefore, the ZrO2 content is 1.5-10%, preferably 2-8%, and more preferably 3-6.5%. In some embodiments, ZrO2 may be included at about 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%.
[0055] In some embodiments, the ratio (K2O+Na2O) / ZrO2 between the total content of K2O and Na2O K2O+Na2O and the content of ZrO2 is controlled within the range of 0.5 to 7.1, the transmittance of the transparent part of the microcrystalline glass and microcrystalline glass products is high, the hardness and Young's modulus of the glass are high, and the dielectric constant of the glass is low. Therefore, preferably (K2O+Na2O) / ZrO2 is 0.5 to 7.1, more preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and further preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5. In some embodiments, the value of (KO+NaO) / ZrO may be 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 6.0, 6.5, 7.0, 7.1.
[0056] In some embodiments, controlling the ratio of Li2O content to ZrO2 content Li2O / ZrO2 within the range of 1.0 to 7.5 can make the glass have a lower refractive index and dielectric loss, can improve the accuracy of pattern formation in microcrystalline glass and microcrystalline glass products after the glass is exposed through a mask and heat treated, and the transparent part of the microcrystalline glass and microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, preferably Li2O / ZrO2 is 1.0 to 7.5, more preferably Li2O / ZrO2 is 1.2 to 5.0, further preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0. In some embodiments, the value of Li2O / ZrO2 may be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5.
[0057] In some embodiments, controlling the ratio (SiO2+Li2O) / ZrO2 between the total content of SiO2 and Li2O SiO2+Li2O and the content of ZrO2 within the range of 8.0 to 55.0 can improve the hardness and drop ball test height of the glass, reduce the expansion coefficient and dielectric constant of the glass, improve the accuracy of pattern formation in the microcrystalline glass and microcrystalline glass products after mask exposure and heat treatment, and improve the drop ball test height of the microcrystalline glass and microcrystalline glass products; the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products is low. Therefore, preferably (SiO2+Li2O) / ZrO2 is 8.0 to 55.0, more preferably (SiO2+Li2O) / ZrO2 is 10.0 to 37.0, further preferably (SiO2+Li2O) / ZrO2 is 12.0 to 25.0, and further preferably (SiO2+Li2O) / ZrO2 is 13.0 to 20.0. In some embodiments, the value of (SiO2+Li2O) / ZrO2 may be 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 47.0, 48.0, 49.0, 50.0, 51.0, 52.0, 53.0, 54.0, 55.0.
[0058] Alkaline earth metal oxide MO (MO is one or more of MgO, CaO, SrO, BaO, and ZnO) can improve the dielectric constant of glass, improve the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products. When the content of MO is higher than 5%, the dielectric constant and dielectric loss of the glass increase, and the Young's modulus and drop ball test height of the glass decrease. Therefore, the content of MO in the present invention is limited to 0-5%, preferably 0-3%, more preferably 0-1%, and further preferably does not contain MO. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2% , 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% MO.
[0059] In some embodiments, when MO / ZrO2 is greater than 2.5, the dielectric loss of the glass increases, the hardness, Young's modulus and drop ball test height of the glass decrease, and the transmittance of the blackened portion of the microcrystalline glass and microcrystalline glass products increases. Therefore, it is preferred that MO / ZrO2 is less than 2.5, more preferably MO / ZrO2 is less than 1.5, and further preferably MO / ZrO2 is less than 0.5. In some embodiments, the value of MO / ZrO2 may be 0, greater than 0, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5.
[0060] CeO2 is a photosensitizer that provides electrons for components such as Ag, Sb, and Sn. When the CeO2 content is lower than 0.01%, it cannot provide enough electrons, resulting in too low a crystal content in the glass-ceramic, reducing the transmittance of the blackened part of the glass-ceramic and glass-ceramic products, and reducing the Young's modulus of the glass-ceramic and glass-ceramic products; when the CeO2 content is higher than 0.6%, the transmittance of the glass-ceramic and glass-ceramic products in the transparent part is reduced, and the penetration depth of the glass-ceramic and glass-ceramic products in the ultraviolet band is reduced, the crystal content inside the blackened part of the glass-ceramic and glass-ceramic products is reduced, and the transmittance is increased. Therefore, the CeO2 content is 0.01-0.6%, preferably 0.07-0.4%, and more preferably 0.08-0.3%. In some embodiments, the present invention may include about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 0.81%, 0.82%, .3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6% CeO2.
[0061] Ag2O, as a crystal nucleating agent for the glass-ceramics and glass-ceramics products of the present invention, plays a role in improving the blackening effect in the glass-ceramics and glass-ceramics products. When the content of Ag2O is less than 0.01%, the transmittance of the blackened part of the glass-ceramics and glass-ceramics products increases, and even cannot be blackened, and the drop ball test height of the glass-ceramics and glass-ceramics products decreases, the expansion coefficient increases, and the graphic accuracy decreases. When the content of Ag2O exceeds 0.8%, the transmittance of the transparent part decreases during the molding or heat treatment of the glass, and due to the excessively high crystal nucleus content, the number of crystals in the glass-ceramics and glass-ceramics products increases, resulting in excessively fine grain size, and the scattering effect of the crystals in the blackened part on visible light is weakened, which easily leads to an increase in the transmittance of the blackened part, and the glass is easy to crystallize during molding. Therefore, the content of Ag2O is limited to 0.01-0.8%, preferably 0.1-0.6%, and more preferably 0.2-0.5%. In some embodiments, the present invention may include about 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0. .4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.6%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.7%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.8% Ag2O.
[0062] The inventors have found that in some embodiments, the ratio of the content of Ag2O to the content of CeO2, Ag2O / CeO2, is controlled within the range of 1.0 to 10.0, and the grain size of the blackened portion of the microcrystalline glass and microcrystalline glass products is larger, the crystal content is higher, the light scattering effect in the visible light band is stronger, the transmittance of the blackened portion is lower, and the hardness and drop ball test height of the microcrystalline glass and microcrystalline glass products are increased. Therefore, preferably Ag2O / CeO2 is 1.0 to 10.0, more preferably Ag2O / CeO2 is 1.5 to 6.5, and further preferably Ag2O / CeO2 is 2.0 to 4.5. In some embodiments, the value of Ag2O / CeO2 can be 1.0, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.
[0063] In some embodiments, the ratio ZrO2 / (Ag2O+CeO2) between the content of ZrO2 and the total content of Ag2O and CeO2 Ag2O+CeO2 is controlled within the range of 2.3 to 50.0, which can optimize the expansion coefficient of the glass, improve the accuracy of the pattern formed in the microcrystalline glass after the glass is exposed through a mask and heat treated, and at the same time, the transparent part of the microcrystalline glass and microcrystalline glass products has a high transmittance, and the blackened part has a low transmittance, and the hardness and ball drop height of the glass and microcrystalline glass products can be improved. Therefore, preferably ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, more preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, further preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0. In some embodiments, the value of ZrO2 / (Ag2O+CeO2) may be 2.3, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5, 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19. 0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 26.0, 27.0, 28.0, 29.0, 30.0, 31.0, 32.0, 33.0, 34.0, 35.0, 36.0, 37.0, 38.0, 39.0, 40.0, 41.0, 42.0, 43.0, 44.0, 45.0, 46.0, 47.0, 48.0, 49.0, 50.0.
[0064] During UV exposure, Sb2O3 and SnO2 absorb Ce 3+ The released electrons play the role of storing electrons and provide Ag for subsequent heat treatment. +Provide electrons to form Ag colloid nucleation and promote the blackening of microcrystalline glass. When the content of Sb2O3+SnO2 is lower than 0.05%, it is difficult for microcrystalline glass or microcrystalline glass products to achieve the blackening effect. When the content of Sb2O3+SnO2 is higher than 1.2%, the blackened part of microcrystalline glass or microcrystalline glass products tends to increase in transmittance. Therefore, the content of Sb2O3+SnO2 is 0.05-1.2%, preferably 0.1-1%, and more preferably 0.2-0.7%. In some embodiments, the content of Sb2O3+SnO2 is about 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1.0%, 1.05%, 1.1%, 1.15%, 1.2%.
[0065] SnO2 has a good effect of promoting the blackening of microcrystalline glass, but in some embodiments, when the content of SnO2 is higher than 0.5%, the transmittance of the transparent part of the glass decreases or even devitrifies during molding or heat treatment. Therefore, the content of SnO2 is limited to 0-0.5%, preferably 0-0.3%, and more preferably 0-0.2%. The content of Sb2O3 is limited to 0-1%, preferably 0.01-0.7%, and more preferably 0.07-0.5%. In some embodiments, the present invention may comprise about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.30%, 0.31%, 0.32%, 0.33%, 0.34%, 0.36%, 0.37%, 0.38%, 0.39%, 0.40%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.50%, 0.51%, 0.52%, 0.53%, 0.54%, 0.55%, 0.56%, 0.57%, 0.58%, 0.59%, 0.60%, 0.61%, 0.62%, 0.63%, 0.64%, 0.65%, 0.66%, 0.67%, 0.68%, 0.69%, 0.70%, 0.71%, 0.72%, 0.73%, 0.74%, 0.75%, 0.76%, 0.77%, 0.78%, 0.79%, 0.80%, 4%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5% SnO2. In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% Sb2O3.
[0066] The inventors have found through a large number of experimental studies that in some embodiments, controlling the ratio of the total content of Sb2O3 and SnO2 Sb2O3+SnO2 to the content of Ag2O (Sb2O3+SnO2) / Ag2O in the range of 0.1 to 5.0 can reduce the dielectric loss of glass, increase the drop ball test height of glass and microcrystalline glass products, and the transparent part of microcrystalline glass and microcrystalline glass products has a higher transmittance, and the blackened part has a lower transmittance. Therefore, preferably (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, more preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and further preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6. In some embodiments, the value of (Sb2O3+SnO2) / Ag2O can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0.
[0067] In some embodiments, by controlling the ratio of the total content of Ag2O, SnO2 and Sb2O3 Ag2O+SnO2+Sb2O3 to the content of CeO2 (Ag2O+SnO2+Sb2O3) / CeO2 within the range of 1.0 to 30.0, the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products can be lowered, thereby reducing the dielectric constant of the glass while increasing the hardness and Young's modulus. Therefore, the preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0~30.0, the more preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0~20.0, the further preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0~12.5, and the further preferred (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5~10.0. In some embodiments, the value of (Ag2O+SnO2+Sb2O3) / CeO2 may be 1.0, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, 13.5, 14.0, 14.5 , 15.0, 15.5, 16.0, 16.5, 17.0, 17.5, 18.0, 18.5, 19.0, 19.5, 20.0, 20.5, 21.0, 21.5, 22.0, 22.5, 23.0, 23.5, 24.0, 24.5, 25.0, 25.5, 26.0, 26.5, 27.0, 27.5, 28.0, 28.5, 29.0, 29.5, 30.0.
[0068] In some embodiments, the ratio of the total content of Sb2O3, SnO2, and CeO2 (Sb2O3+SnO2+CeO2) / Ag2O to the content of Ag2O is controlled within the range of 0.1 to 10.0, which can reduce the dielectric loss and expansion coefficient of the glass and make the transmittance of the blackened part of the microcrystalline glass and microcrystalline glass products lower. Therefore, it is preferred
[0069] (Sb2O3+SnO2+CeO2) / Ag2O is 0.1~10.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4~5.0, further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7~3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5~3.2. In some embodiments, the value of (Sb2O3+SnO2+CeO2) / Ag2O may be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4 , 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.5, 8.0, 8.5, 9.0, 9.5, 10.0.
[0070] In some embodiments, when the value of SnO2 / (CeO2+SnO2) is greater than 0.9, the transmittance of the transparent part of the glass decreases sharply or even completely devitrifies during glass forming or heat treatment. Therefore, preferably SnO2 / (CeO2+SnO2) is 0 to 0.9, more preferably SnO2 / (CeO2+SnO2) is 0 to 0.6, and further preferably SnO2 / (CeO2+SnO2) is 0 to 0.5. In some embodiments, the value of SnO2 / (CeO2+SnO2) can be 0, greater than 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.07, 0.1, 0.13, 0.15, 0.17, 0.2, 0.23, 0.25, 0.27, 0.3, 0.33, 0.35, 0.37, 0.4, 0.43, 0.45, 0.47, 0.5, 0.53, 0.55, 0.57, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73, 0.75, 0.77, 0.8, 0.83, 0.85, 0.87, 0.9.
[0071] Ln2O3 (Ln2O3 is one or more of La2O3, Gd2O3, Y2O3) can adjust the dielectric constant and dielectric loss of the glass, and can be Ag +Provide electrons to promote the blackening of microcrystalline glass. When Ln2O3 is higher than 5%, the transmittance of the blackened part of microcrystalline glass and microcrystalline glass products increases, and the dielectric constant and dielectric loss of the glass increase. Therefore, the content of Ln2O3 is limited to 0-5%, preferably 0-3%, more preferably 0-1%. In some embodiments, it is further preferred that Ln2O3 is not contained. In some embodiments, it may contain about 0%, greater than 0%, 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%, 3.1%, 3.2%, 3.3%, 3.4%, 3.5%, 3.6%, 3.7%, 3.8%, 3.9%, 4%, 4.1%, 4.2%, 4.3%, 4.4%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9%, 5% Ln2O3.
[0072] Fe2O3 can absorb ultraviolet light during the ultraviolet exposure of glass and can be used as Ag + Provide electrons to promote the blackening of glass-ceramics. When the content of Fe2O3 is higher than 1%, the transmittance of the transparent part of glass-ceramics and glass-ceramics products in the visible light band is reduced, the transmittance of the blackened part is increased, and the drop ball test height of glass-ceramics and glass-ceramics products is reduced. Therefore, the content of Fe2O3 is limited to 0-1%, preferably 0-0.5%, more preferably 0-0.2%. In some embodiments, it is further preferred that Fe2O3 is not contained. In some embodiments, the present invention may include about 0%, greater than 0%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3%, 0.31%, 0.32%, 0.33%, 0.34%, 0.35%, 0.36%, 0.37%, 0.38%, 0.39%, 0.4%, 0.41%, 0.42%, 0.43%, 0.44%, 0.45%, 0.46%, 0.47%, 0.48%, 0.49%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% Fe2O3.
[0073] The "does not contain" and "0%" recorded in this article mean that the compound, molecule or element is not intentionally added as a raw material to the matrix glass, microcrystalline glass or microcrystalline glass product of the present invention; however, as the raw materials and / or equipment for producing matrix glass, microcrystalline glass or microcrystalline glass products, there will be certain impurities or components that are not intentionally added, which will be contained in small amounts or trace amounts in the final matrix glass, microcrystalline glass or microcrystalline glass products. This situation is also within the scope of protection of the patent of this invention.
[0074] The various performance indicators of the glass-ceramics and / or glass-ceramics products and / or matrix glass of the present invention are tested by the following methods:
[0075] <Light transmittance>
[0076] The light transmittance is tested according to the following method: the sample to be tested is processed into a certain thickness and the opposite surfaces are polished in parallel, and the test is carried out in accordance with the national standard "GB / T 7962.12-2010".
[0077] <Linear expansion coefficient>
[0078] Linear expansion coefficient (α 20℃-300℃ ) The data of 20°C-300°C are tested according to the national standard "GB / T7962.16-2010". In the present invention, the linear expansion coefficient is sometimes referred to as the expansion coefficient.
[0079] <Dielectric constant>
[0080] Dielectric constant (ε r ) The test was conducted in accordance with the national standard GB / T 7265.1-1987, and the data was tested at 1GHz.
[0081] <Dielectric loss>
[0082] The dielectric loss (tanδ) is tested according to the national standard GB / T 7265.1-1987, and the data is tested under 1GHz conditions.
[0083] <Drop ball test height>
[0084] A φ20×1mm sample is placed on a glass supporting fixture, and a 32g steel ball is dropped from a specified height. The maximum drop ball test height at which the sample can withstand the impact without breaking is the drop ball test height. Specifically, the test is implemented from a drop ball test height of 100mm. Without breaking, the height is changed in sequence through 100mm, 200mm, 300mm, 400mm, 500mm, 600mm, 700mm, 800mm, 900mm, 100mm, 1000mm, 1100mm, 1200mm and above. For the embodiment with "drop ball test height II", the microcrystalline glass product is the test object. The test data recorded as 1000mm in the embodiment indicates that the microcrystalline glass product withstands the impact without breaking even if a steel ball is dropped from a height of 1000mm. For the embodiment with "drop ball test height I", the matrix glass is the test object. The drop ball test height in the present invention is sometimes referred to as the drop ball height.
[0085] <Knoop hardness>
[0086] The load (N) when a diamond quadrangular pyramid indenter with an angle of 172.5° is pressed into a pyramid-shaped depression on the test surface is divided by the surface area (mm2) calculated by the length of the depression. 2 ) value. The test load was 100 (N) and the holding time was 15 (seconds). In the present invention, Knoop hardness may be simply referred to as hardness.
[0087] <Young's modulus>
[0088] Young's modulus (E) is calculated using the following formula by ultrasonic testing of its longitudinal wave velocity and transverse wave velocity.
[0089]
[0090] G=V S 2 ρ
[0091] Where: E is Young's modulus, Pa;
[0092] G is the shear modulus, Pa;
[0093] V T is the shear wave velocity, m / s;
[0094] V S is the longitudinal wave velocity, m / s;
[0095] ρ is the glass density, g / cm 3 .
[0096] <Refractive Index>
[0097] Refractive index (nd ) Tested according to the method specified in GB / T7962.1-2010.
[0098] The matrix glass of the present invention has the following properties:
[0099] 1) In some embodiments, the refractive index (n d ) is 1.51 to 1.55, preferably 1.52 to 1.54, more preferably 1.53 to 1.535, and further preferably 1.53112 to 1.53284.
[0100] 2) In some embodiments, the Young's modulus (E) of the matrix glass of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 Pa.
[0101] 3) In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2 .
[0102] 4) In some embodiments, the drop ball test height I of the matrix glass of the present invention is greater than 200 mm, preferably greater than 300 mm, and more preferably greater than 400 mm.
[0103] 5) In some embodiments, the dielectric loss (tan δ) of the matrix glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 .
[0104] 6) In some embodiments, the dielectric constant (ε r) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0.
[0105] 7) In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.
[0106] The microcrystalline glass of the present invention has the following properties:
[0107] 1) In some embodiments, the average transmittance (T 400-800nm ) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.
[0108] 2) In some embodiments, the average transmittance (T 400-800nm ) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.
[0109] 3) In some embodiments, the transmittance (T 870nm) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.
[0110] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.
[0111] In some embodiments, since the transparent portion of the glass-ceramics of the present invention does not produce crystals, it has the same properties as the above-mentioned matrix glass, such as Young's modulus (E), Knoop hardness (Hk 0.1 ), drop ball test height, dielectric loss (tanδ), dielectric constant (ε r ), linear expansion coefficient (α 20℃-300℃ ) etc. Specifically, in some embodiments, the Young's modulus (E) of the transparent part of the microcrystalline glass of the present invention is 7000×10 7 Pa~9500×10 7 Pa, preferably 7500×10 7 Pa~9200×10 7 Pa, more preferably 7836×10 7 Pa~9014×10 7 Pa, more preferably 8005×10 7 Pa~8488×10 7 In some embodiments, the Knoop hardness (Hk 0.1 ) is 450kgf / mm 2 Above, preferably 470 to 600 kgf / mm 2 , more preferably 480 to 582 kgf / mm 2 , more preferably 492 to 532 kgf / mm 2In some embodiments, the drop ball test height of the transparent part of the microcrystalline glass of the present invention is 200 mm or more, preferably 300 mm or more, and more preferably 400 mm or more. In some embodiments, the dielectric loss (tan δ) of the transparent part of the microcrystalline glass of the present invention is 11.0×10 -3 Below, preferably 7.0×10 -3 ~10.5×10 -3 , more preferably 7.2×10 -3 ~9.8×10 -3 , and more preferably 7.4×10 -3 ~9.2×10 -3 In some embodiments, the dielectric constant (ε r ) is 5.5 to 8.5, preferably 6.0 to 8.0, more preferably 6.2 to 7.7, and further preferably 6.3 to 7.0. In some embodiments, the linear expansion coefficient (α 20℃-300℃ ) is 100×10 -7 / ℃ or less, preferably 65×10 -7 / ℃~100×10 -7 / ℃, more preferably 71×10 -7 / ℃~95×10 -7 / ℃, more preferably 75×10 -7 / ℃~90×10 -7 / ℃.
[0112] The microcrystalline glass product of the present invention has the following properties:
[0113] 1) In some embodiments, the average transmittance (T 400-800nm ) is 85.0% or more, preferably 88.0% or more, more preferably 90.0% or more, further preferably 91.0% or more, and further preferably 91.5 to 95.0%. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.
[0114] 2) In some embodiments, the average transmittance (T 400-800nm) is 5.0% or less, preferably 3.0% or less, more preferably 1.5% or less, further preferably 1.2% or less, and further preferably 0.5% or less. The thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.
[0115] 3) In some embodiments, the transmittance (T 870nm ) is less than 15.0%, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, 1.2 mm.
[0116] 4) In some embodiments, the transmittance (T 940nm ) is less than 50.0%, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%. The above thickness is preferably 0.5 to 1.5 mm, more preferably 0.8 to 1.2 mm, and further preferably 0.5 mm, 0.7 mm, 0.8 mm, 0.9 mm, 1.0 mm, 1.1 mm, and 1.2 mm.
[0117] 5) In some embodiments, the drop ball test height II of the microcrystalline glass product of the present invention is greater than 800 mm, preferably greater than 900 mm, more preferably greater than 1000 mm, and further preferably greater than 1100 mm.
[0118] In some embodiments, the matrix glass / microcrystalline glass / microcrystalline glass product of the present invention has a lower dielectric constant and dielectric loss, which can reduce the transmission loss of electrical signals.
[0119] In some embodiments, the matrix glass / glass-ceramics / glass-ceramics articles of the present invention have relatively high Knoop hardness, Young's modulus and ball drop height.
[0120] In some embodiments, the matrix glass / glass-ceramic / glass-ceramic product of the present invention has a lower linear expansion coefficient to improve the accuracy of the optical signal channel or mask pattern.
[0121] In some embodiments, the matrix glass / glass-ceramics / glass-ceramics products of the present invention have a relatively low refractive index, which can reduce the reflectivity of surface light signals and increase the incidence of light signals.
[0122] The microcrystalline glass, microcrystalline glass products, and matrix glass of the present invention can be widely made into glass cover plates or glass components due to the above-mentioned excellent properties; at the same time, the microcrystalline glass, microcrystalline glass products, matrix glass of the present invention, and glass cover plates or glass components made thereof can be used to manufacture various instruments or equipment, including but not limited to electronic equipment, medical equipment, decorations or handicrafts, such as mobile phones, watches, computers, biomedical detection, etc., for manufacturing local light shielding glass or patterned cover glass for mobile phones, smart phones, tablet computers, laptops, televisions, etc., or optical signal channel glass for smart watches, biomedical devices, etc., or for manufacturing patterned decorations or handicrafts glass.
[0123] The matrix glass, glass-ceramics and glass-ceramics products of the present invention can be produced and manufactured by the following methods:
[0124] The manufacturing method of the matrix glass comprises the following steps: weighing the raw materials according to the component ratio and mixing them uniformly, placing the uniformly mixed raw materials into a platinum or quartz crucible, melting, clarifying, homogenizing and then cooling at 1450-1600°C, pouring the molten glass liquid into a mold for forming, and introducing circulating cooling air to ensure that the glass does not crystallize, preferably preheating the mold to 200-500°C, placing the formed glass and the mold into an annealing furnace for heat preservation and annealing, and then turning off the power and cooling with the furnace to obtain the matrix glass.
[0125] The manufacturing method of microcrystalline glass includes the following steps: forming a matrix glass, treating the matrix glass through a crystallization process, or processing the matrix glass into a glass element of a specific shape and then treating it through a crystallization process to obtain the microcrystalline glass of the present invention. The method of processing a glass element of a specific shape of the present invention includes methods known to those skilled in the art such as hot pressing, grinding or polishing. The crystallization process treatment of the present invention includes mask exposure treatment of the matrix glass, and then crystallization heat treatment, and uniformly precipitating crystals at the glass exposure position. The mask exposure treatment of the present invention refers to ultraviolet exposure at a specific position or area of the matrix glass, and the ultraviolet light wavelength is preferably 313nm. A special photomask pattern can be customized according to application requirements, and the exposure time is preferably 5 to 60 minutes. The crystallization heat treatment of the present invention can be carried out in one stage or in two stages, and preferably in two stages. The two-stage crystallization heat treatment refers to performing a nucleation process at a first temperature and then performing a crystal growth process at a second temperature higher than the nucleation process temperature. Preferably, the first temperature is 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. Preferably, the second temperature is 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.
[0126] The manufacturing method of the glass-ceramic product comprises the following steps: treating the glass-ceramic of the present invention by a chemical strengthening process, or processing the glass-ceramic into a glass-ceramic element of a specific shape and then treating it by a chemical strengthening process, to obtain the glass-ceramic product of the present invention. The method of processing into a specific shape of the present invention includes hot pressing, grinding or polishing, etc., which are known to those skilled in the art.
[0127] The chemical strengthening described in the present invention is an ion exchange method. During the ion exchange process, smaller metal ions in the glass-ceramics are replaced or "exchanged" by larger metal ions with the same valence state near the glass-ceramics. The replacement of smaller ions with larger ions builds up compressive stress in the glass-ceramics, forming a compressive stress layer.
[0128] In some embodiments, the metal ion is a monovalent alkali metal ion (e.g., Na + , K + , Rb + , Cs + Ion exchange is performed by immersing the glass-ceramic in a salt bath of at least one molten salt containing larger metal ions, which are used to replace smaller metal ions in the glass-ceramic. Alternatively, other monovalent metal ions such as Ag + , Tl + , Cu +The one or more ion exchange processes used to chemically strengthen the glass-ceramic may include, but are not limited to, immersing it in a single salt bath, or immersing it in multiple salt baths of the same or different compositions, with washing and / or annealing steps added between immersions.
[0129] In some embodiments, the glass-ceramics can be ion exchanged by immersing in a salt bath of molten Na salt (such as NaNO3), and / or K salt (such as KNO3), and / or a mixed salt of Na and K at a temperature of about 350°C to 470°C for 1 to 36 hours, preferably in the temperature range of 380°C to 460°C, and preferably in the time range of 2 to 24 hours.
[0130] In some embodiments, the matrix glass of the present invention can be processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed into a glass-ceramic product by the above-mentioned crystallization process. In some embodiments, the matrix glass of the present invention can be processed into a glass element, and then the glass element is processed into a strengthened glass by the above-mentioned chemical strengthening process, and then processed into a glass-ceramic product by the above-mentioned crystallization process.
[0131] Example
[0132] In order to further clearly illustrate and describe the technical solution of the present invention, the following non-limiting examples are provided. The present invention embodiments have been tried to ensure the accuracy of the values (such as quantity, etc.), but some errors and deviations must be taken into account. The composition itself is given in weight % based on the oxide and has been standardized to 100%.
[0133] <Matrix Glass Example>
[0134] This embodiment adopts the above-mentioned method for manufacturing the matrix glass to obtain the matrix glass having the composition shown in Tables 1 to 4. In addition, the properties of each matrix glass are measured by the test method described in the present invention, and the measurement results are shown in Tables 1 to 4.
[0135] Table 1.
[0136]
[0137]
[0138] Table 2.
[0139]
[0140]
[0141] Table 3.
[0142]
[0143]
[0144] Table 4.
[0145]
[0146]
[0147] <Glass-ceramic Example>
[0148] This embodiment adopts the above-mentioned method for manufacturing microcrystalline glass to obtain microcrystalline glass having the composition shown in Tables 5 to 8. In addition, the characteristics of each microcrystalline glass are measured by the testing method described in the present invention, and the measurement results are shown in Tables 5 to 8. The transmittance of the microcrystalline glass in the following embodiments is tested using a 1 mm thick sample.
[0149] Table 5.
[0150]
[0151]
[0152] Table 6.
[0153]
[0154]
[0155] Table 7.
[0156]
[0157]
[0158] Table 8.
[0159]
[0160]
[0161] <Glass-ceramic product example>
[0162] This embodiment adopts the manufacturing method of the above-mentioned microcrystalline glass products to obtain microcrystalline glass products having the compositions shown in Tables 9 to 12. In addition, the characteristics of each microcrystalline glass product are measured by the testing method described in the present invention, and the measurement results are shown in Tables 9 to 12. The transmittance of the microcrystalline glass products in the following embodiments is tested using a 1 mm thick sample.
[0163] Table 9.
[0164]
[0165]
[0166] Table 10.
[0167]
[0168]
[0169] Table 11.
[0170]
[0171]
[0172] Table 12.
[0173]
[0174]
Claims
1. A method for manufacturing a glass-ceramic product, characterized in that: The method comprises the following steps: forming a matrix glass, subjecting the matrix glass to a crystallization process to form a microcrystalline glass, and then subjecting the microcrystalline glass to a chemical strengthening process to form a microcrystalline glass product, wherein the crystallization process comprises subjecting the matrix glass to a mask exposure process and then to a crystallization heat treatment.
2. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The microcrystalline glass product comprises one or more blackened parts and one or more transparent parts. The average transmittance T of the transparent part of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm in the wavelength range of 400 to 800 nm is 400-800nm The average transmittance T of the blackened part of the 0.2-1.5 mm thick microcrystalline glass product in the 400-800 nm band is 85.0% or more. 400-800nm It is less than 5.0%.
3. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The mask exposure process includes ultraviolet exposure of a specific position or area of the substrate glass, the wavelength of the ultraviolet light is preferably 313 nm, and the exposure time is preferably 5 to 60 minutes.
4. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The crystallization heat treatment is carried out in two stages, and the two-stage crystallization heat treatment includes a nucleation process at a first temperature, and then a crystal growth process at a second temperature higher than the nucleation process temperature. The first temperature is preferably 490°C to 520°C, and the first temperature treatment time is preferably 1 to 4 hours. The second temperature is preferably 540°C to 620°C, and the second temperature treatment time is preferably 1 to 8 hours.
5. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The chemical strengthening process includes immersing the microcrystalline glass in a salt bath of molten Na salt, and / or K salt, and / or a mixed salt of Na and K at a temperature of 350°C to 470°C for about 1 to 36 hours, preferably at a temperature of 380°C to 460°C, and preferably for 2 to 24 hours.
6. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: Average transmittance T of the transparent part of 0.2-1.5mm thick microcrystalline glass products in the 400-800nm band 400-800nm is 88.0% or more, preferably 90.0% or more, more preferably 91.0% or more, and further preferably 91.5-95.0%; and / or the average transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2-1.5 mm in the 400-800 nm wavelength range 400-800nm is 3.0% or less, preferably 1.5% or less, more preferably 1.2% or less, and further preferably 0.5% or less; and / or the transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm at 870 nm 870nm is 15.0% or less, preferably 0.1 to 12.5%, more preferably 0.1 to 10%, further preferably 0.1 to 8.0%, and further preferably 0.1 to 5.0%; and / or the transmittance T of the blackened portion of the microcrystalline glass product with a thickness of 0.2 to 1.5 mm at 940 nm 940nm It is 50.0% or less, preferably 0.1 to 35.0%, more preferably 0.3 to 20.0%, further preferably 0.3 to 15.0%, and further preferably 0.3 to 10.0%.
7. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The blackened part of the microcrystalline glass product contains a crystalline phase, and the transparent part of the microcrystalline glass product does not contain a crystalline phase.
8. The method for manufacturing a glass-ceramic product according to claim 7, characterized in that: The blackened portion of the microcrystalline glass product contains a lithium metasilicate crystalline phase. In the blackened portion of the microcrystalline glass product, the weight percentage of the lithium metasilicate crystalline phase is preferably 5 to 50%, more preferably 5 to 40%, and further preferably 10 to 30%.
9. The method for manufacturing a glass-ceramic product according to any one of claims 1 to 8, characterized in that: The components of the microcrystalline glass product are expressed by weight percentage, comprising: SiO2: 65-78%, preferably SiO2: 68-77%, more preferably SiO2: 69.5-75.5%; R2O: 2-12%, preferably R2O: 3-10%, more preferably R2O: 4-8%; Li2O: 5-15%, preferably Li2O: 7-13%, more preferably Li2O: 8.5-12%; Al2O3: 3-12%, preferably Al2 O3: 4-10%, more preferably Al2O3: 5-9%; ZrO2: 1.5-10%, preferably ZrO2: 2-8%, more preferably ZrO2: 3-6.5%; CeO2: 0.01-0.6%, preferably CeO2: 0.07-0.4%, more preferably CeO2: 0.08-0.3%; Ag2O: 0.01-0.8%, preferably Ag2O: 0.1-0.6%, more preferably Ag2O: 0.2-0.5% ; Sb2O3: 0-1%, preferably Sb2O3: 0.01-0.7%, more preferably Sb2O3: 0.07-0.5%; SnO2: 0-0.5%, preferably SnO2: 0-0.3%, more preferably SnO2: 0-0.2%; MO: 0-5%, preferably MO: 0-3%, more preferably MO: 0-1%, further preferably containing no MO; Ln2O3: 0-5%, preferably Ln2O3: 0-3%, more preferably Ln2 O3: 0-1%, and it is further preferred that Ln2O3 is not contained; Fe2O3: 0-1%, preferably Fe2O3: 0-0.5%, more preferably Fe2O3: 0-0.2%, and it is further preferred that Fe2O3 is not contained, the R2O is one or two of Na2O and K2O, MO is one or more of MgO, CaO, SrO, BaO, and ZnO, and Ln2O3 is one or more of La2O3, Gd2O3, and Y2O3.
10. The method for manufacturing a glass-ceramic product according to any one of claims 1 to 9, characterized in that: The components of the microcrystalline glass product are expressed in weight percentage and meet one or more of the following 14 conditions: 1) SiO2 / Li2O is 5.5 to 10.0, preferably SiO2 / Li2O is 6.0 to 9.0, and more preferably SiO2 / Li2O is 7.0 to 8.5; 2) (Sb2O3+SnO2) / Ag2O is 0.1 to 5.0, preferably (Sb2O3+SnO2) / Ag2O is 0.5 to 3.5, and more preferably (Sb2O3+SnO2) / Ag2O is 1.0 to 2.6; 3) (K2O+Na2O) / ZrO2 is 0.5 to 7.1, preferably (K2O+Na2O) / ZrO2 is 0.7 to 4.5, and more preferably (K2O+Na2O) / ZrO2 is 0.8 to 2.5; 4) Ag2O / CeO2 is 1.0 to 10.0, preferably Ag2O / CeO2 is 1.5 to 6.5, and more preferably Ag2O / CeO2 is 2.0 to 4.5; 5) Li2O / ZrO2 is 1.0 to 7.5, preferably Li2O / ZrO2 is 1.2 to 5.0, more preferably Li2O / ZrO2 is 1.4 to 4.3, and further preferably Li2O / ZrO2 is 1.6 to 3.0; 6) (SiO2 + Li2O) / ZrO2 is 8.0 to 55.0, preferably (SiO2 + Li2O) / ZrO2 is 10.0 to 37.0, more preferably (SiO2 + Li2O) / ZrO2 is 12.0 to 25.0, and further preferably (SiO2 + Li2O) / ZrO2 is 13.0 to 20.0; 7) ZrO2 / (Ag2O+CeO2) is 2.3 to 50.0, preferably ZrO2 / (Ag2O+CeO2) is 6.5 to 35.0, more preferably ZrO2 / (Ag2O+CeO2) is 8.5 to 20.0, and further preferably ZrO2 / (Ag2O+CeO2) is 11.0 to 18.0; 8) (Ag2O+SnO2+Sb2O3) / CeO2 is 1.0 to 30.0, preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 3.0 to 20.0, more preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 5.0 to 12.5, and further preferably (Ag2O+SnO2+Sb2O3) / CeO2 is 7.5 to 10.0; 9) (Sb2O3+SnO2+CeO2) / Ag2O is 0.1 to 10.0, preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.4 to 5.0, more preferably (Sb2O3+SnO2+CeO2) / Ag2O is 0.7 to 3.7, and further preferably (Sb2O3+SnO2+CeO2) / Ag2O is 1.5 to 3.2; 10) SnO2 / (CeO2+SnO2) is 0 to 0.9, preferably SnO2 / (CeO2+SnO2) is 0 to 0.6, and more preferably SnO2 / (CeO2+SnO2) is 0 to 0.5; 11) R2O+Li2O+Al2O3 is 15-30%, preferably R2O+Li2O+Al2O3 is 17.5-29.5%, more preferably R2O+Li2O+Al2O3 is 18.5-26%, and further preferably R2O+Li2O+Al2O3 is 20-25%; 12) (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.0 to 7.5, preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 3.7 to 6.5, more preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.3 to 6.0, and further preferably (SiO2+Al2O3) / (Li2O+Na2O+K2O) is 4.8 to 5.8; 13) MO / ZrO2 is 2.5 or less, preferably MO / ZrO2 is 1.5 or less, and more preferably MO / ZrO2 is 0.5 or less; 14) Sb2O3+SnO2: 0.05-1.2%, preferably Sb2O3+SnO2: 0.1-1%, more preferably Sb2O3+SnO2: 0.2-0.7%, wherein R2O is one or two of Na2O and K2O, and MO is one or more of MgO, CaO, SrO, BaO and ZnO.
11. The method for manufacturing a glass-ceramic product according to claim 1, characterized in that: The drop ball test height II of the microcrystalline glass product is 800 mm or more, preferably 900 mm or more, more preferably 1000 mm or more, and further preferably 1100 mm or more.
12. A glass-ceramic product, characterized in that: The microcrystalline glass product is manufactured by the manufacturing method of any one of claims 1 to 11.
13. A glass cover plate, characterized in that: A microcrystalline glass product comprising the glass-ceramic product according to claim 12.
14. A device, characterized in that A microcrystalline glass product comprising the glass product according to claim 12, and / or a glass cover plate according to claim 13.